2021
DOI: 10.1002/csc2.20457
|View full text |Cite
|
Sign up to set email alerts
|

Inbred and hybrid sweet corn genotype performance in diverse organic environments

Abstract: The value of selection in conventional breeding trials of cultivars destined for organic systems depends on the correlation between systems and relative heritability of key traits. Genotype by environment interactions is a common phenomenon in plant breeding trials. Thus, multienvironment testing to identify stable genotypes is a high priority for organic systems. In addition, This article is protected by copyright. All rights reserved. because organic systems have limited inputs to buffer the environment, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 36 publications
(52 reference statements)
1
21
0
1
Order By: Relevance
“…The material tested in this project was based on 40 high‐quality sugary enhancer1 sweet corn inbreds from the University of Wisconsin sweet corn program or on progeny derived from them. These inbred represent a substantial fraction of the diversity of the most elite sugary enhancer1 material from the program (Zystro et al., 2020b).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The material tested in this project was based on 40 high‐quality sugary enhancer1 sweet corn inbreds from the University of Wisconsin sweet corn program or on progeny derived from them. These inbred represent a substantial fraction of the diversity of the most elite sugary enhancer1 material from the program (Zystro et al., 2020b).…”
Section: Methodsmentioning
confidence: 99%
“…Hybrids were developed based on four disconnected North Carolina Design II (NC DII) mating blocks, each with five males and five females (Zystro et al., 2020a). Crosses were made such that (a) inbreds with shared pedigrees (Zystro et al., 2020b) were not crossed to each other, (b) each mating block contained no inbreds with shared pedigrees, and (c) each mating block had inbreds that shared a common pedigree with at least one other inbred in each of the other three blocks.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the results of this study are unique to this set of germplasm. Many of the inbred entries used to create both the hybrids in the NC DII training sets and the hybrids in the validation set share common ancestors (Zystro et al, 2020). When studying population structure and accuracy of genomic selection in wheat (Triticum aestivum L.), Isidro et al (2015) found that accuracy was highest when the training and test populations are highly related.…”
Section: Crop Sciencementioning
confidence: 99%